Shifting from rice production to shrimp culture in coastal zones of Khulna: Determination of the determinants - Anisuzzaman, M; Islam, MA; Rahman, KMM; Shetu, MSR (Journal of the Bangladesh Agricultural University, 2016)
This study aimed to investigate the determinants of shifting to shrimp culture from rice cultivation in coastal zones of Khulna district by using primary data collected from the four upazillas of Khulna, namely, Batiaghata, Dacope, Dumuria, and Paikgacha. Along with bivariate analysis, single-level binary logistic regression was carried out to identify the determinants of shifting. Through the bivariate analysis it had found that among all variables considered, some variables, precisely, amount of land holdings, access to credit, contact with GOs/NGOs, intrusion of saline water, perception of profitability of shrimp, and water logging had significant relation with shifting to shrimp culture. Similarly, the binary logistic regression had identified five significant determinants of shifting from rice cultivation to shrimp culture: occupation, land holding, access to credit, intrusion of saline water, and water logging. J. Bangladesh Agril. Univ. 13(2): 257-264, December 2015